The Influence of Cigarette Tax Sharing and Realization Local Revenue effect to Budgeting Policy on Revenue Service Financial Management and Asset Soppeng Regency - Andi Asmy Nurhikmah; mattalatta - (Jurnal Mirai Management, 2016)
ABSTRACT The aim of the study 1) to determine effect for additional cigarette tax revenue sharing funds to budgetary policy at the Department of Revenue Financial Management and Asset Soppeng Regency, 2) to detemine effect in local revenue realization of the budgetary policy at the Department of Revenue Financial Management and Asset Soppeng Regency. This research was conducted in the Office of Financial Management Revenue and Asset Soppeng Regency using financial statement data. Analysis of the data used is the analysis of different test two average through the program Statistical Package For Social Science (SPSS) .21. The results of hypothesis testing in this study shows that 1) there are influences in the addition of cigarette tax revenue sharing funds to budgetary policy, 2) there are influences in the realization of local revenue to service revenue budgeting policy on financial management and asset Soppeng Regency. Keywords : Cigarette Tax Revenue Sharing, Realization of Local Revenue, Budgeting Policy.